Thermal Comfort and Learning Experience on Semi-Outdoor Space of Nature-Based Schools: A Scoping Review - Dadang Hartabela; Cipta Vidyana; Rendy Perdana Khidmat; Novita Hillary Christy Damanik; Indah Prastiwi (Jurnal Arsitektur, 2026)
Nature-based schools increasingly adopt semi-outdoor learning spaces to support experiential education, yet thermal conditions may affect children's learning and well-being. This scoping review maps current evidence on thermal comfort, children's thermal adaptation, and learning outcomes in semi-outdoor educational settings using the PRISMA-ScR framework. Total of 42 studies were included. Studies were classified into two evidence tiers: 13 core studies involving children or school environments and 29 contextual studies on outdoor thermal comfort in parks, campuses, and streets that informed transferable design principles. Core evidence suggests that children demonstrate behavioural and psychological adaptations that partially alleviate thermal discomfort, while excessive heat is generally associated with reduced concentration and academic performance. Contextual evidence identifies mean radiant temperature, shading, and vegetation as key passive cooling strategies. These findings underscore the importance of climate-responsive educational design and emphasize the need for longitudinal, child-focused research using appropriate thermal comfort indices.